Visual language for designers : principles for creating graphics that people understand - Malamed, Connie (Rockport Publishers, 2009)
Within every picture is a hidden language that conveys a message, whether it is intended or not. This language is based on the ways people perceive and process visual information. By understanding visual language as the interface between a graphic and a viewer, designers and illustrators can learn to inform with accuracy and power. In a time of unprecedented competition for audience attention and with an increasing demand for complex graphics, Visual Language for Designers explains how to achieve quick and effective communications. This book presents ways to design for the strengths of our innate mental capacities and to compensate for our cognitive limitations. Visual Language for Designers includes: -How to organize graphics for quick perception -How to direct the eyes to essential information -How to use visual shorthand for efficient communication -How to make abstract ideas concrete -How to best express visual complexity -How to charge a graphic with energy and emotion.